Recovery from repeated on-court tennis sessions: combining cold-water immersion, compression, and sleep interventions - Duffield, R.; Murphy, A. P.; Kellett, A. D.; Reid , M. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To investigate the effects of combining cold-water immersion (CWI), full-body compression garments (CG), and sleep-hygiene recommendations on physical, physiological, and perceptual recovery after 2-a-day on-court training and match-play sessions. Methods: In a crossover design, 8 highly trained tennis players completed 2 sessions of on-court tennis-drill training and match play, followed by a recovery or control condition. Recovery interventions included a mixture of 15 min CWI, 3 h of wearing full-body CG, and following sleep-hygiene recommendations that night, while the control condition involved postsession stretching and no regulation of sleeping patterns. Technical performance (stroke and error rates), physical performance (accelerometry, countermovement jump [CMJ]), physiological (heart rate, blood lactate), and perceptual (mood, exertion, and soreness) measures were recorded from each on-court session, along with sleep quantity each night. Results: While stroke and error rates did not differ in the drill session (P > .05, d < 0.20), large effects were evident for increased time in play and stroke rate in match play after the recovery interventions (P > .05, d > 0.90). Although accelerometry values did not differ between conditions (P > .05, d < 0.20), CMJ tended to be improved before match play with recovery (P > .05, d = 0.90). Furthermore, CWI and CG resulted in faster postsession reductions in heart rate and lactate and reduced perceived soreness (P > .05, d > 1.00). In addition, sleep-hygiene recommendations increased sleep quantity (P > .05, d > 2.00) and maintained lower perceived soreness and fatigue (P < .05, d > 2.00). Conclusions: Mixed-method recovery interventions (CWI and CG) used after tennis sessions increased ensuing time in play and lower-body power and reduced perceived soreness. Furthermore, sleep-hygiene recommendations helped reduce perceived soreness.